PENGARUH KONSENTRASI MEDIA KACANG KEDELAI(Glycine max L. Merr) DALAM PERTUMBUHAN BAKTERI Staphylococcus aureus DIBANDINGKAN DENGAN NUTRIENT - Siregar, Sa’adah; Rizky, Vincentia Ade; Nasution, Salmiah (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Soybean is a complete protein, inexpensive and is one of the food ingredients that contain groups of essential and non-essential amino acids, carbohydrates, fats, vitamins and minerals. Staphylococcus is coccus bacteria, gram positive with an irregular arrangement or clusters like grapes. Staphylococcus aureus is a bacterium that is non-spore, non-motile, facultative anaerobe, oxidase negative and catalase positive. The aim of the study was to determine the growth of Staphylococcus aureus bacteria in alternative media for soybeans as a substance for Nutrient agar media. The type of experimental research is to conduct a trial on the concentration of soy bean powder. research  population of soybeans purchased at Lubuk Pakam market. Is an experimental method for the growth of staphylococcus aureus bacteria in soybean media as a substitute for Nutrient agar. Of research from soybeans (Glycine max L. Merr) can be used as an alternative source of protein in the manufacture of alternative media, but have slight differences in the size of the colony, the color of the colony and the color of the pigment produced with varying concentrations of 20%, 40%, 60% and 80%.  Soybeans are effectively used as an alternative protein source to replace Nutrient agar media in growing Staphylococcus aureus bacteria for a more effective concentration, namely at a concentration of 60% when viewed from the number of colonies obtained in the soybean media